2018
DOI: 10.1128/iai.00849-17
|View full text |Cite
|
Sign up to set email alerts
|

The cGAS/STING Pathway Detects Streptococcus pneumoniae but Appears Dispensable for Antipneumococcal Defense in Mice and Humans

Abstract: is a frequent colonizer of the upper respiratory tract and a leading cause of bacterial pneumonia. The innate immune system senses pneumococcal cell wall components, toxin, and nucleic acids, which leads to production of inflammatory mediators to initiate and control antibacterial defense. Here, we show that the cGAS (cyclic GMP-AMP [cGAMP] synthase)-STING pathway mediates detection of pneumococcal DNA in mouse macrophages to primarily stimulate type I interferon (IFN) responses. Cells of human individuals car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…Recognition by DNA sensors is a prerequisite for triggering type I IFN response, in which cGAS has a critical role. It has also been reported that cGAS is involved in the expression of IFN-b mediated by S. pn or mtDNA [15,36]. We found that STING deletion impaired the expression of Ply-induced type I IFNs, and we detected increased phosphorylation of the STING downstream element IRF3.…”
Section: Discussionsupporting
confidence: 77%
“…Recognition by DNA sensors is a prerequisite for triggering type I IFN response, in which cGAS has a critical role. It has also been reported that cGAS is involved in the expression of IFN-b mediated by S. pn or mtDNA [15,36]. We found that STING deletion impaired the expression of Ply-induced type I IFNs, and we detected increased phosphorylation of the STING downstream element IRF3.…”
Section: Discussionsupporting
confidence: 77%
“…To investigate if pneumococcal c-di-AMP could be a modulator of type I interferon responses, RAW264.7 macrophage-like cells were infected with the phosphodiesterase mutants and mRNA was collected so that IFNβ expression could be measured. We expected one of three outcomes: consistently elevated IFNβ responses across the mutant pneumococci, matching the observations with NF-κB activity ( Figure 1); a ramping up of IFNβ responses with peak levels after infection by the double mutant pde1 pde2 strain, based on how c-di-AMP content in pneumococci increase due to phosphodiesterase mutations (26); or no effect of phosphodiesterase mutation, based on the postulate that pneumococcal DNA but not c-di-AMP drives IFNβ responses (19). Surprisingly, macrophage IFNβ responses matched none of these expectations.…”
Section: Mixed Macrophage Ifnβ Responses To the Phosphodiesterase Mutmentioning
confidence: 55%
“…STING is an adaptor molecule and receptor for cyclic dinucleotides in the cytosol including the bacterial metabolites cyclic di-GMP and cyclic di-AMP (c-di-AMP), as well as the mammalian-derived cyclic GMP-AMP (cGAMP) produced by the cyclic GMP-AMP synthase (cGAS) enzyme (16)(17)(18). Induction of IFNβ by pneumococcus requires both STING and cGAS (19), which was interpreted as evidence that pneumococcal DNA but not pneumococcal c-di-AMP triggers STING-dependent IFNβ induction (19). However, a cGAS-STING complex is essential to IFNβ induction by purified c-di-AMP (20), which could contribute to the requirement for cGAS in pneumococcus-induced signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Immune Cells Homozygous for STING-R231H but Not STING-HAQ Respond to Endogenous 2 ′ 3 ′ cGAMP STING plays a central role in intracellular DNA sensing pathways by binding the cGAS product 2 ′ 3 ′ cGAMP, resulting in IRF3 activation. Previous work suggested that STING-HAQ is a null allele, disabling the carrier's ability to respond to 2 ′ 3 ′ cGAMP (29), although others have reported residual ability of PBMCs of STING-HAQ/HAQ carriers to respond to intracellular DNA or cGAMP (38,39). We incubated heterozygous and homozygous STING-HAQ B cells with increasing concentrations of 2 ′ 3 ′ cGAMP.…”
Section: Heterozygous Sting-haq B Cells and Sting-r231h B Cells Have mentioning
confidence: 99%